PERANCANGAN SISTEM INFORMASI PENDISTRIBUSIAN (STUDI KASUS PADA PT.TRIMITRA ARGA MULIA CILEGON) - Syaechurodji Syaechurodji; Rizki Fatullah (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
PT. Trimitra Arga Mulia is one of the companies engaged in the Distribution of Drinking Water, where drinking water is really needed by all people, especially in urban areas. The purpose of writing this report is to find out how the system used by the company is there many obstacles or not. The method used by the author is by direct observation to the field, question and answer with employees and leaders, and look for books related to distribution. After conducting observations on the company, the authors found weaknesses such as when employees make deliveries to each route with drivers that have been determined, then stock gallons in warehouses and data collection of new and outgoing customers, and data processing, causing data inaccuracies. These weaknesses are determined because the system is still semi computerized. From the results of research conducted by the author, it is concluded that it is necessary to hold an improved system that has been integrated with the database in processing data and in making reports.